Designing an innovative SEO marketing plan to promote Indonesian tourism using AI-driven tool - Koswara, Asep; Marpuah, Siti (Indonesian Tourism Journal, 2024)
This study adopts the descriptive research method to design an innovative SEO marketing plan aimed at promoting Indonesian tourism using AI-driven tools, specifically SEO.AI. The objective is to explore how artificial intelligence can be leveraged for enhancing keyword generation, content creation, and overall SEO optimization to boost the visibility of Indonesian destinations on global search engines. The research identifies high-volume tourism-related keywords like Bali, Komodo Island, and Raja Ampat and develops a step-by-step SEO strategy, including AI-powered content generation, website optimization, and link-building techniques. Through this process, the study demonstrates the effectiveness of AI-driven tools in streamlining SEO tasks and improving search engine rankings, providing practical implications for the tourism industry. The findings suggest that using AI for SEO can significantly enhance the digital presence of Indonesian tourism. However, the research also acknowledges certain limitations, such as dynamic search trends and external influences on tourism. Future studies are recommended to explore additional digital marketing strategies and assess the long-term impact of AI-driven SEO methods on tourism marketing.